Moroccan Muslim students' cultural and religious diversity recognition in Spanish schools. A critical multiculturalism analysis from their mothers' perspectives - Torres-Zaragoza, Lucia (Frontiers in Education, 2025)
IntroductionWestern schools are characterized by its increasing heterogeneity. However, they often fail to address cultural and religious diversity, specially of minority groups. Muslim migrant students' identities tend to be overlooked, which affects their feelings of belonging and inclusion.MethodsThis study aims to analyze Moroccan Muslim migrant mothers' perceptions of the way their cultural and religious diversity is addressed in schools. A qualitative research with a critical multiculturalism approach is adopted. Semi-structured interviews were conducted to a total of 12 participants, selected with a purposeful sampling.ResultsSome teachers do not address cultural and religious diversity in the classroom, adopting pedagogies of the indifference. Cultural diversity celebrations are unusual and focus on superficial aspects such as customs and food. Accommodations measures are found as a way to address religious diversity. Nevertheless, no religious diversity celebrations were reported. While Muslim religious celebrations were overlooked, there was a privilege for catholic celebrations, that organized the school calendar and activities. Mothers suggested lessons for all the students to learn from their culture and religion to increase understanding.DiscussionIn conclusion, there is a need for more teacher training, better curriculum specifications and inter-cultural and interreligious practices that foster social cohesion and inclusion.